The Pain System in Oesophageal Disorders: Mechanisms, Clinical Characteristics, and Treatment - Christian Lottrup; Søren Schou Olesen; Asbjørn Mohr Drewes (Gastroenterology Research and Practice)
Pain is common in gastroenterology. This review aims at giving an overview of pain mechanisms, clinical features, and treatment options in oesophageal disorders. The oesophagus has sensory receptors specific for different stimuli. Painful stimuli are encoded by nociceptors and communicated via afferent nerves to the central nervous system. The pain stimulus is further processed and modulated in specific pain centres in the brain, which may undergo plastic alterations. Hence, tissue inflammation and long-term exposure to pain can cause sensitisation and hypersensitivity. Oesophageal sensitivity can be evaluated ,for example, with the oesophageal multimodal probe. Treatment should target the cause of the patient's symptoms. In gastro-oesophageal reflux diseases, proton pump inhibitors are the primary treatment option, surgery being reserved for patients with severe disease resistant to drug therapy. Functional oesophageal disorders are treated with analgesics, antidepressants, and psychological therapy. Lifestyle changes are another option with less documentation.